Serviço social, educação popular e relações de gênero: um diálogo entre os três saberes na busca da emancipação - Biasi, Ana Soraia Haddad (Universidade do Vale do Rio do Sinos, 2007)
The present dissertation is the result of a study accomplished starting from the experience in popular education lived in the carrying out of my social work profession, of the life narratives that I obtained in the interviews made with five social workers of the Municipal district of Chapecó, SC and of the readings that I accomplished, during this master's degree. This movement passed from the feminist perspective to popular education, and it provoked a dialogue among social service, popular education and gender relationships, aiming to identify a policy proposal of social emancipation for the strengthening of the subjects in the amplification and consolidation of citizenship with a view to guaranteeing human rights. In spite of the complexity in the practice of the social work profession we know, that the professional performance is deeply concentrated in the social interests of antagonistic classes whose historical development happened for the most part, starting from the feminine perspective for problems o
Keywords: cidadania; relações de gênero; serviço social; educação popular; citizenship; gender relationships; social service; popular education; Ciências Humanas